Correlation of Time Since Death with Morphological Changes in Neutrophils (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Death is the end of dying. It is a process rather than an event except in the exceptionally rare situations where death may be almost instantaneous [1]. Materials & Methods: In this study morphological changes in neutrophils were studied in autopsy cases. Blood samples from 57 different autopsy cases were taken and smears were prepared after staining them with Leishman stain. The samples were examined using light microscope under 40X and 100X magnification. Results: Among 57 cases no degenerative changes were seen in 8. Mild degenerative changes were seen in among 23, Moderate among 12 and Marked among 14 cases. Among 57 cases while observing degenerative changes in neutrophils nuclear changes were seen in 47 cases in form of pyknosis among them 40 reached to level of nuclear fragmentation. Cytoplasmic changes were seen in form of cytoplasmic vacuolation seen in 49 cases. Among them loss of cytoplasm was seen in 36 and cytoplasmic degeneration seen in 26. There was only 8 case in which no change was seen. No changes were seen upto 6 hrs. Conclusion: The present study proves that changes in the morphology of neutrophils can be helpful as supplementary procedure for estimating time since death.
Keywords: Morphological changes; White blood cells; Lysis; Time since death